Chronic hepatitis C virus infection and lipoprotein metabolism - Aizawa, Yoshio (World J Gastroenterol, 2015)
Hepatitis C virus (HCV) is a hepatotrophic virus and a major cause of chronic liver disease, including hepatocellular carcinoma, worldwide. The life cycle of HCV is closely associated with the metabolism of lipids and lipoproteins. The main function of lipoproteins is transporting lipids throughout the body. Triglycerides, free cholesterol, cholesteryl esters, and phospholipids are the major components of the transported lipids. The pathway of HCV assembly and secretion is closely linked to lipoprotein production and secretion, and the infectivity of HCV particles largely depends on the interaction of lipoproteins. Moreover, HCV entry into hepatocytes is strongly influenced by lipoproteins. The key lipoprotein molecules mediating these interactions are apolipoproteins. Apolipoproteins are amphipathic proteins on the surface of a lipoprotein particle, which help stabilize lipoprotein structure. They perform a key role in lipoprotein metabolism by serving as receptor ligands, enzyme co-factors, and lipid transport carriers. Understanding the association between the life cycle of HCV and lipoprotein metabolism is important because each step of the life cycle of HCV that is associated with lipoprotein metabolism is a potential target for anti-HCV therapy. In this article, we first concisely review the nature of lipoprotein and its metabolism to better understand the complicated interaction of HCV with lipoprotein. Then, we review the outline of the processes of HCV assembly, secretion, and entry into hepatocytes, focusing on the association with lipoproteins. Finally, we discuss the clinical aspects of disturbed lipid/lipoprotein metabolism and the significance of dyslipoproteinemia in chronic HCV infection with regard to abnormal apolipoproteins.